2020
DOI: 10.1111/head.13923
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Headaches During Covid‐19 Infection: A Retrospective Cohort Study

Abstract: Objectives.-To document the prevalence of new headaches in patients with Covid-19 infection and the potential association with other neuro-sensorial symptoms (anosmia and ageusia). The persistence of these symptoms 1 month after recovery was also documented. Background.-Headaches are a very common symptom of viral infections. Surprisingly, early Chinese studies reported a relatively low prevalence (12-15%) of headaches associated with Covid-19. Methods.-All the patients with laboratory-confirmed or chest-CT-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
0
4

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 16 publications
3
93
0
4
Order By: Relevance
“…Ten studies included people requiring ICU admission during the acute phase. [9,[25][26][27][28][29][30][31][32] The longest follow-up period in any study was a mean of 111 (SD: 11) days post-discharge (Table 2). Most studies did not specify covid-19 severity nor treatment received during the acute phase.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies included people requiring ICU admission during the acute phase. [9,[25][26][27][28][29][30][31][32] The longest follow-up period in any study was a mean of 111 (SD: 11) days post-discharge (Table 2). Most studies did not specify covid-19 severity nor treatment received during the acute phase.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Most studies did not specify covid-19 severity nor treatment received during the acute phase. Pre-existing comorbidities were reported in half of the studies (54%, 15/28), [9,25,[27][28][29][30][31][33][34][35][36][37][38] with hypertension and diabetes most commonly documented. Symptoms A wide range of new or persistent symptoms were documented in both the hospitalised and non-hospitalised cohorts.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 102 , 103 , 107 , 108 The recovery of these symptoms is still undetermined; i.e., it is not yet known whether it is total or partial and what the recovery times are. 103 , 109 , 110 And this question refers to what is perhaps the most important question: will there be neurological sequelae in the medium-to-long-term? Incomplete resolution of chemosensory alterations could indicate future neurodegenerative diseases, as these symptoms are prognostic symptoms of many neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…After having carried out two tests, which must be negative, as the literature suggests [ 30 ], for the diagnosis of a recovered patient, it is essential to know why some studies [ 31 , 32 ] have reported that after having obtained these two negative tests, patients present symptoms and present in some cases positivity of new tests. Because this phenomenon has been described in different countries [ 24 , 33 , 34 ], it is discussed that cannot be attributed only to false negatives due to the coincides with others studies, so it could be a reactivation or reinfection [ 30 ].…”
Section: Introductionmentioning
confidence: 99%